Cartographic representation of the efficiency of distribution of primary education services in Al-Maimuna District for the year 2021 - Awadh, Murtadha (Al-Adab Journal, 2023)
The study research includes the representation of primary education services in the district of Al-Maimuna maps, and modern technologies have been used in the use of information and data in the preparation of maps with high accuracy in drawing, design and information as well as deduction, updating and analysis, the research has indicated that the total number of primary schools in the district of Al-Maimuna for the year 2021 ( 101 ) schools, the center of elimination ranked first with the largest number of schools and then the side of peace in second place while the area of Sayed Ahmed Rifai came in The third and last rank, and the research proved that the number of primary schools is not commensurate with the number of students in the judiciary according to the global standard for the number of students in one class, through this study it was concluded that the district of Maimuna needs (13) schools for the purpose of achieving the ideal number of schools.